COLD REGULATED 27 and 28 are targets of CONSTITUTIVELY PHOTOMORPHOGENIC 1 and negatively affect phytochrome B signalling. (27th September 2020) - Kahle, Nikolai; Sheerin, David J.; Fischbach, Patrick; Koch, Leonie‐Alexa; Schwenk, Philipp; Lambert, Dorothee; Rodriguez, Ryan; Kerner, Konstantin; Hoecker, Ute; Zurbriggen, Matias D.; Hiltbrunner, Andreas
SUMMARY: Phytochromes are red/far‐red light receptors in plants involved in the regulation of growth and development. Phytochromes can sense the light environment and contribute to measuring day length; thereby, they allow plants to respond and adapt to changes in the ambient environment. Two well‐characterized signalling pathways act downstream of phytochromes and link light perception to the regulation of gene expression. The CONSTITUTIVELY PHOTOMORPHOGENIC 1/SUPPRESSOR OF PHYA‐105 (COP1/SPA) E3 ubiquitin ligase complex and the PHYTOCHROME INTERACTING FACTORs (PIFs) are key components of these pathways and repress light responses in the dark. In light‐grown seedlings, phytochromes inhibit COP1/SPA and PIF activity and thereby promote light signalling. In a yeast‐two‐hybrid screen for proteins binding to light‐activated phytochromes, we identified COLD‐REGULATED GENE 27 (COR27). COR27 and its homologue COR28 bind to phyA and phyB, the two primary phytochromes in seed plants. COR27 and COR28 have been described previously with regard to a function in the regulation of freezing tolerance, flowering and the circadian clock. Here, we show that COR27 and COR28 repress early seedling development in blue, far‐red and in particular red light. COR27 and COR28 contain a conserved Val‐Pro (VP)‐peptide motif, which mediates binding to the COP1/SPA complex. COR27 and COR28 are targeted for degradation by COP1/SPA and mutant versions with a VP to AA amino acid substitution in the VP‐peptide motif are stabilized. Overall, our data suggest that COR27 and COR28 accumulate in light but act as negative regulators of light signalling during early seedling development, thereby preventing an exaggerated response to light. Significance Statement: COR27 and COR28 have previously been shown to play a role in cold and circadian clock regulated responses. Here, we describe a function of COR27 and COR28 in photomorphogenesis and phytochrome‐dependent early seedling development and show that they are targets of the COP1/SPA E3 ubiquitin ligase complex.